USING STUDENT-CENTERED LEARNING METHOD IN IMPROVING STUDENTS’ GRAMMAR ABILITY - Reski, Ade Ervina; Korompot, Chairil Anwar; Muhayyang, Maemuna (Universitas Negeri Makassar, 2023)
This research aimed to find out whether using the SCL method is effective in improving students’ grammar ability or not. The researcher used a one-shot case study as the research design with treatment and post-test which consisted of 30 multiple-choice grammar tests. This research was conducted at SMA Negeri 19 Gowa in the eleventh grade with a total population of 214 students. The sample was Class XI IIS 2 with a total of 34 students selected using random sampling technique. The research data was analyzed quantitatively using a paired sample t-test. The mean score of the pre-test was 68.80 and the post-test was 84.80. The data showed the increased score after the sample received treatment and based on the sig. value (2-tailed) was 0.00 < 0.05. It can be concluded that using student-centered learning was effective in improving students’ grammar ability.